تجليات المكان في رواية نجوى بن شتوان (Journal of Academic Research, 2024)
Praise be to God, Lord of the Worlds, and may blessings and peace be upon the most honorable of the prophets and messengers, our Master Muhammad the Truthful and Trustworthy, and upon all his family and companions.And after: The Libyan novel has witnessed great development, which has made it impose itself on the genres of Arabic writing during the Libyan literary scene. However, this does not deny the presence of fluctuation in the novelistic process. However, anyone who contemplates the movement of criticism and creativity notices the emergence of indicators and signs indicating the flourishing of this art, which embodies... In the emergence of some novelist names that have begun to impose themselves as novelists, such as: Ibrahim Al-Koni, Abdullah Al-Ghazal, and Ahmed Al-Faqih in this field, Najwa Bin Shatwan’s novel is considered a textual space towards which the study is moving, as its events take place in an area between Ajdabiya and Fezzan in a street called Abdullah Al-Abs Street. To tell the story of a girl named ((Awisha)).